SIFAT FISIK DAN MEKANIK TIGA JENIS POHON PIONIR - Sudin Panjaitan; Yatno Yuwono; Yeni Nuraeni (Jurnal Riset Industri Hasil Hutan, 2013)
This research was conducted were to determine physical and mechanical characteristics of three pioneer tree species namely : Macaranga hosei, Macaranga hypoleuca and Endospermum diadenum;  to determine the effect of species differences on the physical and mechanical characteristic of the woods. the result showed that : Maximum water content and dry weight  of the species were Endospermum diadenum (115,627 %; 12,15 %), Macaranga hosei (156,534 %; 12,49 %) and Macaranga hypoleuca (171,510 % and  12,49 %), respectively,  Average bulk density in wet volume, dry volume and tenure dry volume were Endospermum diadenum (0,323 (Vb); 0,346 (Vku); 0,378 (Vkt), Macaranga hosei (0,261 (Vb); 0,278 (Vku); 0,300 (Vkt) and Macaranga hypoleuca (0,296 (Vb); 0,315 (Vku); 0,338 (Vkt), respectively, The shrinking dry weight-tenure weight were Endospermum diadenum (6,91 %; 14,47 %), Macaranga hosei (6,43 %; 12,87 %), and Macaranga hypoleuca (6,40 % and 12,33 %), respectively,  The statical elasticity strength were Endospermum diadenum (372,220 kg/cm2), Macaranga hosei (282,490 kg/cm2) and Macaranga hypoleuca (261,490 kg/cm2), respectively, Fiber strength were Endospermum diadenum (63,360 kg/cm2), Macaranga hosei (40,800 kg/cm2), Macaranga hypoleuca (34,618 kg/cm2).Kata kunci : physical,  mechanical,  pioneer wood